QUALITATIVE METHODS OF CRIMINAL LAW RESEARCH: UKRAINIAN AND FOREIGN EXPERIENCE - Semchuk, Natalya O.; Timush, Diana I. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The purpose of this article is to assess the most common methods of conducting qualitative (as opposed to quantitative) research in the field of criminal law, used by Ukrainian and foreign researchers, for their compliance with the basic characteristics. For this purpose, such methods as the method of doctrinal analysis were used, and in addition other theoretical and empirical research methods, such as historical, qualitative analysis of documents, etc. Results: based on the analysis of works of domestic and foreign scholars, it is substantiated that the basis for the science of criminal law is a normative analysis of the law (doctrinal analysis), which includes efforts to understand the best balance of rights and responsibilities. Ukrainian researchers know this method as system (method of system-structural analysis). Discussion: legal research is defined as research focused on extrapolating legal norms to specific cases. Scientific «discovery» in the field of law involves careful analysis and creative synthesis of various legal norms of doctrine, concept or principles and evaluation of legal doctrines or law, it must be combined with analytical skills and interaction with deduction and induction during such analysis.